A phase 1b study of venetoclax and azacitidine combination in patients with relapsed or refractory myelodysplastic syndromes. Issue 2 (10th November 2022) - Zeidan, Amer M.; Borate, Uma; Pollyea, Daniel A.; Brunner, Andrew M.; Roncolato, Fernando; Garcia, Jacqueline S.; Filshie, Robin; Odenike, Olatoyosi; Watson, Anne Marie; Krishnadasan, Ravitharan; Bajel, Ashish; Naqvi, Kiran; et al.
Abstract: Patients with relapsed/refractory (R/R) higher‐risk myelodysplastic syndromes (MDS) have a dismal median overall survival (OS) after failing hypomethylating agent (HMA) treatment. There is no standard of care for patients after HMA therapy failure; hence, there is a critical need for effective therapeutic strategies. Herein, we present the safety and efficacy of venetoclax + azacitidine in patients with R/R MDS. This phase 1b, open‐label, multicenter study enrolled patients ≥18 years. Patients were treated with escalating doses of oral venetoclax: 100, 200, or 400 mg daily for 14 days every 28‐day cycle. Azacitidine was administered on Days 1–7 every cycle at 75 mg/m 2 /day intravenously/subcutaneously. Responses were assessed per modified 2006 International Working Group (IWG) criteria. Forty‐four patients (male 86%, median age 74 years) received venetoclax + azacitidine treatment. Median follow‐up was 21.2 months. Hematological adverse events of Grade ≥ 3 included febrile neutropenia (34%), thrombocytopenia (32%), neutropenia (27%), and anemia (18%). Pneumonia (23%) was the most common Grade ≥ 3 infection. Marrow responses were seen including complete remission (CR, n = 3, 7%) and marrow CR (mCR, n = 14, 32%); 36% (16/44) achieved transfusion independence (TI) for RBCs and/or platelets, and 43% (6/14) with mCR achieved hematological improvement (HI). The median time to CR/mCR was 1.2 months, and the median duration of response for CR + mCR was 8.6 months. Median OS was 12.6 months. Venetoclax + azacitidine shows activity in patients with R/R MDS following prior HMA therapy failure and provides clinically meaningful benefits, including HI and TI, and encouraging OS.